Synthetic Analogue of Leu-Enkephalin Prevents Endothelial Dysfunction in vitro - O. A. Grebenchikov; A. M. Ovezov; Yu. V. Skripkin; T. S. Zabelina; O. N. Ulitkina; A. V. Lugovoy; A. S. Prikhodko; A. Yu. Ryzhkov; R. A. Zinovkin (Общая реаниматология)
The purpose of the study was to determine the efficacy of a synthetic leu-enkephalin stabilized analogue to prevent damage of endothelial cells monolayer in vitro caused by serum samples from septic shock patients.Materials and methods. The experiments were performed using the EaHy.926 endothelial cells monolayer. We studied the in vitro effect of synthetic leu-enkephalin analogue on the cell damage caused by serum samples from five septic shock patients. The status of endothelial intercellular junctions was estimated by immunofluorescence microscopy and western blot with antibodies against adherens junction protein, VE-cadherin, and against the tight junctions protein, claudin. Cell viability was determined by staining with propidium iodide.Results. Preconditioning with a synthetic leu-enkephalin analogue (10, 50 and 100 μg/ml) of endothelial cells in vitro prevented the destruction of both tight and adherens junction and partially prevented endothelial cell death.Conclusion. Preconditioning with a synthetic leu-enkephalin analogue partially prevents endothelial cell damage caused by exposure to septic patients’ sera in vitro. These data ensure the need for clinical trials on the effectiveness of a synthetic leu-enkephalin analogue for prevention of sepsis-associated endothelial dysfunction in clinics.